Versatility of Streptomyces sp. M7 to bioremediate soils co-contaminated with Cr(VI) and lindane - Aparicio, Juan Daniel (2015)
The aim of this work was to study the impact of environmental factors on the bioremediation of Cr(VI) and lindane contaminated soil, by an actinobacterium, Streptomyces sp. M7, in order to optimize the process.Soil samples were contaminated with 25μgkg-1 of lindane and 50mgkg-1 of Cr(VI) and inoculated with Streptomyces sp. M7. The lowest inoculum concentration which simultaneously produced highest removal of Cr(VI) and lindane was 1gkg-1. The influence of physical and chemical parameters was assessed using a full factorial design. The factors and levels tested were: Temperature: 25, 30, 35°C; Humidity: 10%, 20%, 30%; Initial Cr(VI) concentration: 20, 50, 80mgkg-1; Initial lindane concentration: 10, 25, 40μgkg-1.Streptomyces sp. M7 exhibited strong versatility, showing the ability to bioremediate co-contaminated soil samples at several physicochemical conditions. Streptomyces sp. M7 inoculum size was optimized. Also, it was fitted a model to study this process, and it was possible to predict the system performance, knowing the initial conditions. Moreover, optimum temperature and humidity conditions for the bioremediation of soil with different concentrations of Cr(VI) and lindane were determined. Lettuce seedlings were a suitable biomarker to evaluate the contaminants mixture toxicity. Streptomyces sp. M7 carried out a successful bioremediation, which was demonstrated through ecotoxicity test with Lactuca sativa